Novel Homeodomain Transcription Factor Nkx2.2 in the Brain Tumor Development - Mariyath, Mubeena P.M.; Shahi, Mehdi H.; Farheen, Shirin; Tayyab, Mohd; Khanam, Nabeela; Ali, Asif (Current Cancer Drug Targets, 2020)
Background: Complex central nervous system (CNS) is made up of neuronal cells and glial cells. Cells of central nervous system are able to regenerate after injury and during repairing. Sonic hedgehog pathway initiated by Shh-N a glycoprotein plays vital role in CNS patterning growth, development and now tumorigenesis. Nkx2.2 homeodomain transcription factor is an effecter molecule, which is positively regulated by Shh during normal growth. Nkx2.2 is essential for V3 domain specification during neural tube patterning at embryonic stage. MBP + oligodendrocytes are differentiated from progenitor cells which express Olig2. Nx2.2 is co-expressed with Olig2 in oligodendrocytes and is essential for later stage of oligodendrocyte maturation. Objective: This review paper explores the potential role of Nkx2.2 transcription factor in glioblastoma development. Conclusion: Shh pathway plays a vital role in oligodendrocytes differentiation and Nkx2.2 transcription factor is essential for oligodendrocytes differentiation and maturation. Intriguingly, down regulation of Nkx2.2 transcription factor with aberrant Shh signaling pathway is reported in glioma samples. So here it is suggested that Nkx2.2 expression pattern could be used as a potential biomarker for the early diagnosis of glioma.
Keywords: Nkx2.2